VLF/LF signal studies of the ionospheric response to strong seismic activity in the Far Eastern region combining the DEMETER and ground-based observations. (2015) - Rozhnoi, A.; Solovieva, M.; Parrot, M.; Hayakawa, M.; Biagi, P.-F.; Schwingenschuh, K.; Fedun, V.
Highlights: The ground-based and DEMETER VLF data were processed using the same a method. The method of residual signal for the strong earthquakes in the Far East was used. The ground and satellite observations demonstrated good coincidence of results. Abstract: The paper presents the results of a joint analysis of ground-based and satellite observations of very low-frequency and low-frequency (VLF/LF) signals during periods of strong seismic activity in the region of Kuril Islands and Japan in 2004–2010. Ground and satellite data was processed using a method based on the difference between the real signal in nighttime and that of a model. The results of the analysis show a good correlation between ground-based and satellite data for several cases of strong ( M  ⩾ 6.8) earthquakes.